Parlamentary Elections in the District of Berane in 1920 and 1923 - Deletić, Zdravko M.; Virijevic, Vladan R. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
The lack of more significant political tradition due to the fact that Berane and the area of Donji Vasojevici were liberated from the Ottoman authorities in 1912, which lasted for many centuries, as well as the fact that only three years later a two-year period of Austro-Hungarian occupation took place, mainly predetermined the atmosphere of political life in the first years after Yugoslav unification in 1918. The underdevelopment of the party organizations and grouping based on denominational, tribal and even on belonging to some brotherhood, were characteristic for the beginnings of political subjects in Berane district. These were party organizations whose headquarters were settled in Belgrade, Sarajevo and Skopje and whose leaders were as in the case of other districts in the province, often resorted to emphasizing their candidature in them. There were also the individuals on the local political scene, mostly teachers or the civil servants, who were representatives of the party’s ideas and programme in their surrounding and therefore also the incumbent candidates of their lists. During parliamentary elections in Berane in 1920 and 1923 the main political rivalry was between members of the radical and democratic party while it was characterised by fragmentation of the party namely emphasizing „dissident“ candidate list as the consequences of political ambitions of the individuals. Regarding the results of elections in 1920 and 1923, generally speaking, it can be said that during the first half of the 20s of the last century Democratic party dominated in Berane district. Berane got „its“ Member of the Parliament – “a democrat“ Pavle Cubrovic, PhD while in 1923 it no longer had its representative in the parliament. Namely, despite Cubrovic’s triumph in Berane district, since his candidate list did not get enough votes in the first round of elections, the position of the Member of the Parliament “escaped“ him.